The journey has just begun - William Lekse (RAE: Revista de Administração de Empresas, 2019)
This special issue contributes to incorporating research utilizing Big data—in particular, the disciplines of information systems and supply chain—into mainstream academic research. It also extends Big data’s contribution to establishing predictive analytics-based research as theory building. Big data brings many features to academic research that, if properly understood, can shift the approach of most research towards that of the classical academic approach, which focuses on building and testing theory. The academic approach to theoretical research seeks to explain phenomena by applying frameworks, which are sourced from different disciplines such as microeconomics, operations research, organizational theory, psychology, and sociology.